Emotional Responses in Clinical Ethics Consultation Decision-Making: An Exploratory Study - Margherita Dahò (Behavioral Sciences)
Integrating Clinical Ethics Consultants (CECs) into healthcare requires understanding how they apply bioethical knowledge while managing cognitive and emotional challenges in ethical deliberations. Ethical consultations often elicit strong emotions, yet their impact on decision-making remains underexplored. This study explores the emotional responses of 52 CECs from the United States and 10 European countries through a semi-structured survey. Participants selected a real ethical case they had encountered and described their emotional reactions during and after deliberation. Findings revealed that almost 77% of CECs experienced negative emotions such as frustration, sadness, or anger during deliberation, while 21% reported neutral or positive feelings. Although satisfaction and relief increased after deliberation, negative emotions often persisted. Additionally, 45% of participants reported feelings of inadequacy or remorse, 12% expressed uncertainty about their decision, and 5% stated they would change their decision in hindsight. The accumulation of negative emotions may affect CECs’ well-being and judgment, highlighting the need for structured support. Managing cognitive and emotional demands is essential to maintaining CECs’ effectiveness, underscoring the importance of targeted training programs and support strategies to enhance ethical decision-making and resilience in high-stakes medical contexts.